Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis PBL untuk Meningkatkan Hasil Belajar Fisika - Kholida Ismatulloh; Yosi Nur Kholisho; Bq. Malika Hr; Baiq Desi Dwi Arianti (Kappa Journal, 2024)
This research aims to determine the effectiveness and response of students to the Student Worksheet (LKPD) that was developed. The type of research is research and development with a "one group pretest-posttest design". Population in this research were class VIII students at SMP 3 Selong. The instruments used are interview sheets, observation sheets, product validation, student response questionnaire sheets, teacher response questionnaire sheets, learning device validation sheets, evaluation question sheets. The research results were analyzed using the method quantitative descriptive. The results of the analysis of pre-test and post-test evaluation questions increased, showing an average N-gain 0.70 with an average pre-test score of 23.97 and an average post-test score of 81.47. The t test results show that t calculated > t (0.05)(66), namely 30.40 > 1.66. This indicates that Problem Base Learning (PBL) based LKPD is effective in improving students' physics learning outcomes.